RANCANG BANGUN SISTEM SMS GATEWAY SEBAGAI FASILITAS PERMOHONAN CUTI KARYAWAN - Maimunah Maimunah; Supra Singgih; Anwar Supriyadi (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
The development of information technology is growing rapidly one of which involves natural resources (HR) employees at the company scope for example, employees at this time, felt increasingly required by each agency. One of the functions required in the processing of human resources in the processing of employee leave, the PT bermuda comunication engaged in appertising manufacturing services stickers, pins, posters, flyers,banners, x-banner, roll banner, one way vision, blocknot, every company must give entitlement to karyawanya. Problems that occur before the leave still use manual, so it is necessary to leave the computerized management process. In meeting these conditions, built a facility employee leave request system based SMS Gateway application. The system is built using Gammu software using PHP programming language as early as the lawyersubmitted data input is stored in a MySQL database, then connected with the concept of client-server suite in Osi layers, and output results utilizing sms gateway facilities. With a system of employee leave application for SMS-based Gateway is the employee leave theservice process becomes easier and faster. The process of filing, checking and decision making employee leave entitlements can be carried out systematically. In addition, the leave application process could be more transparent.